Challenges in Diagnosis of Neurosarcoidosis - Ekladious Adel (Journal of Spine and Neuroscience, 2024)
Sarcoidosis is granulomatous autoinflammatory autoimmune remitting relapsing disease affecting every organ in the body, it is the most difficult disease to diagnose in the absence of serum or imaging biomarker. Differential diagnosis is broad which included inflammatory, infective, neurodegenerative and neoplastic, histological biopsy is the only confirmative marker, and even histological confirmation is not robust as infection, malignancy and some drugs can induce granuloma, the most common organs affected are lung, lymph nodes, skin, eyes, liver, and less commonly pituitary gland, bones, brain, peripheral nerves, and heart, causing bilateral hilar lymphadenopathy, granulomatous lymphadenitis.
Keywords: Sarcoidosis